ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT BAGI HASIL TABUNGAN DEPOSITO MUDHARABAH PADA PERBANKAN SYARIAHDI INDONESIA PERIODE 2012 -2016 - Halimatussa’idah Halimatussa’idah; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this research is to analyze the effect of Non Performing Financing,Operational Efficiency Ratio, BI Rate and inflation toward the rate of return mudharabah deposits islamic bank industries in Indonesia start from January 2012 until December 2016. This research use quantitative approach. The analysis method used in this research is time series regression using eviews 9.0 program. This research used saturation sampling. Sample that used in this research were taken from Islamic Bank Statistic issued by OJK, while BI Rate and Inflation taken from www.bi.go.id. The result show that Non Performing Financinghas no effect on the rate of return mudharabah deposits, Beban Operasional Pendapatan Operasional has no effect on the rate of return mudharabah deposits. While BI Rate has positive and significant on the rate of return mudharabah deposits, and than variabel inflation has negative and significant on the rate of return mudharabah deposits. All of the independent variables in this research are simultaniosly significant on the rate of return mudharabah deposits.Keywords: Non Performing Financing(NPF), Operational Efficiency Ratio (BOPO), BI Rate, inflation, the rate of return mudharabah depositsREFFERENCESAntonio, Muhammad Syafii. (2017). Bank Syariah dari Teori ke Praktik.Jakarta : Gema Insani.Arif, Mohammad Nur Rianto Al. (2011).The Effect Of Macro Economic On Profit – Sharing Yield Pricing. Yogyakarta : Economic Journal Of Emerging Markets. Vol.3.No 3. Hlm 234 – 244.Bank Indonesia.(2006). Peraturan Bank Indonesia Nomor 8/21/PBI/2006.Jakarta : Bank Indonesia._____________. (2007). Lampiran Surat Edaran Bank Indonesia Nomor 9/24/DPbs/2007.Jakarta : Bank Indonesia._____________. (2001). Peraturan Bank Indonesia Nomor 3/25/PBI/2001.Jakarta : Bank Indonesia._____________. (2011). Surat Edaran Bank Indonesia Nomor 13/24/DPNP 25 Oktober 2011.Jakarta : Bank Indonesia.Chong, Beng Soon dan Liu, Ming-Hua. (2008). Islamic Banking : Interest Free or Interest-Based?. Elsevier : Pasific-Basin Financing Journal 125 – 144.Departemen Agama, RI. (2012). The Noble Qur’an. Depok : Al-Huda Kelompok Gema Insani.Dewan Syariah Nasional MUI.(2000). Fatwa DSN Nomor 03/DSN-MUI/2000 Tentang Deposito.Jakarta : Dewan Syariah Nasional MUI.Djamil, Faturrahman.(2014).Penyelesaian Pembiayaan Bermasalah di Bank Syariah. Jakarta : Sinar Grafika.Farianto, Agus. (2014). Analisis Pengaruh Return On Asset (ROA), BOPO dan BI Rate Terhadap Tingkat Bagi Hasil Deposito Mudharabah Pada Bank Umum Syariah di Indoneisa Tahun 2012 – 2013. Kudus : Equilibrium. Vol 2. No.1 Ghozali, Imam. (2011). Aplikasi Analisis Multivariate dengan Program IBM SPSS 19.Semarang : Badan Penerbit Universitas Diponegoro.Hamza, Hichem. (2015) .Does Investment Deposit Return in Islamic Bank Reflects PLS Principle?.Eelsevier : Borsa Istanbul Review 16-1 32-42.Sudarsono, Heri. (2009) .Dampak Krisis Keuangan Global Terhadap Perbankan di Indonesia : Perbandingan Antara Bank Konvensional dan Bank Syariah. Yogayakarta : La Riba Jurnal Ekonomi Islam. Vol 3. No 1.Ismail.(2014). Perbankan Syariah.Jakarta : Kencana Prenada Media.K, Andryani Isna dan Sunaryo, Kunti.(2012). Analisis Pengaruh Return On Asset, BOPO dan Suku Bunga Terhadap Tingkat Bagi Hasil Deposito Mudharabah Pada Bank Umum Syariah. Yogyakarta : Jurnal Ekonomi dan Bisnis. Vol. 11 No.1.Karim, Adiwarman A, dan Affif, Adi Zakaria.(2005). Islamic Banking Consumer Behaviour in Indonesia: A Qualitative Approach. Jakarta : Karim Business Consulting.Karim, Adiwarman A, (2016). Bank Islam Analisis Fiqih dan Keuangan.Jakarta : PT. Raja Grafindo Persada.Latumaerissa, Julius R. (2012). Bank dan Lembaga Keuangan Lain.Jakarta : Salemba Empat.Muhammad. (2011). Manajemen Bank Syariah.Yogyakarta : Unit Penerbitan dan Percetakan sekolah tinggi ilmu manajemen YKPN.Nofianti, Nana. dkk. (2015). Analisis Pengaruh ROA, BOPO, Suku Bunga, FDR dan NPF terhadap Tingkat Bagi Hasil Deposito Mudharabah.Banten : Esensi Jurnal Bisnis dan Mnajemen Vol.5.No.1.___________________. (2012). Statistik Perbankan Syariah.Jakarta : Otoritas Jasa Keuangan.___________________. (2013). Statistik Perbankan Syariah.Jakarta : Otoritas Jasa Keuangan.___________________. (2014). Statistik Perbankan Syariah.Jakarta : Otoritas Jasa Keuangan.___________________. (2015). Statistik Perbankan Syariah.Jakarta : Otoritas Jasa Keuangan.___________________. (2016). Statistik Perbankan Syariah.Jakarta : Otoritas Jasa Keuangan.Santoso, Singgih. (2000). Buku Latihan SPSS : Statistik Parametrik. Jakarta : PT. Elex Media KomputindoSolissa, Nuriyah Diyan. (2017). Profit Equalization Reserve (PER) Sebagai Upaya Mitigasi Risiko Imbal Hasil Perbankan Syariah. Yogyakarta: Az Zarqa’, Vol. 9, No. 1, Juni 2017.Sudarsono, Heri. (2002). Bank dan Lembaga Keuangan Syariah Deskripsi dan Illustrasi.Jakarta : Ekonosia.Sugiyono. (2015). Metode Penelitian Kuantitatif, Kualitatif dan R & D. Bandung : Alfabeta.Ulfah, Rizakia. (2011). Pengaruh Makro Ekonomi Terhadap Penetapan Nisbah Bagi Hasil Deposito Mudharabah Perbankan Syariah di Indonesia.Skripsi.Jakarta : Uin Syarif Hidayatullah.Undang – Undang Republik Indonesia Nomor 21 Tahun 2008 Tentang Perbankan Syariah.Undang – Undang Republik Indonesia Nomor 10 Tahun 1998 Tentang Perbankan.